414 Informed Consent for Neck of Femur Fracture Surgery During the Covid-19 Pandemic: An Evidence-Based Approach. (12th October 2021) - Cuthbert, R; Ferguson, D; Kayani, B; Haque, S; Ali, A; Parkar, A; Bates, P; Vemulapalli, K
Abstract: Background: Surgical intervention for neck of femur fractures continues to be prioritised during the Covid-19 pandemic. However, there remains a lack of clarity for clinicians during the consent process. This study quantifies additional perioperative risks for Covid-19 positive patients undergoing neck of femur fracture surgery and establishes an evidence-based framework for facilitating informed consent during the Covid-19 pandemic. Method: 259 patients undergoing neck of femur fracture surgery in four hospitals at the epicentre of the United Kingdom's first wave of Covid-19 were recruited. 51 patients were positive for Covid-19. Predefined outcomes were recorded in a 30-day postoperative period. Results: Odds of intensive care admission were 4.64 times higher (95% CI 1.59-13.50, p = 0.005) and odds of 30-day mortality were 3 times higher (95% CI 1.22-7.40, p = 0.02) in Covid-19 positive patients. 74.5% of Covid-19 positive patients suffered post-operative complications. 35.3% of Covid-19 positive patients developed lower respiratory tract infection with 13.7% progressing to acute respiratory distress syndrome. 9.8% of Covid-19 positive patients experienced symptomatic thromboembolic events with a 3.9% incidence of pulmonary emboli. Conclusions: The implications of Covid-19 on the informed consent process for neck of femur fracture surgery are profound. Covid-19 positive patients should be consented for increased risk of postoperative complications (including lower respiratory tract infection, acute respiratory distress syndrome and thromboembolic events), longer inpatient stay, increased frequency of intensive care admission and higher risk of mortality.